Visões de práticas dos formadores do curso de Ciências Biológicas da UFG - FERREIRA, Daniela Rodrigues Macedo (2010)
The theme of this work is the university teaching and the main objective is to understand how some professors that are part of the teaching formation in biological sciences of Goias s Federal University (UFG) conceive their practices and what formative experiences they are able to offer to their future students. Since it is a study of a group of professors in a specific course, in a higher educational institution, this survey is characterized as a study case upon a qualitative approach, which seeks to identify the different points of view of practice opposing to the complexity of teacher formation. During the discussions many aspects which are related to the main theme of this work were addressed: a historical overview beginning with the creation of the Brazilian University and the teaching formation at university, and public policies that had been influenced this process directly, such as the guidelines for the undergraduate, in particular the degree in biological sciences. Among the theoretical bibliographies that substantiate these discussions were both national and international contributions. National literature: Masetto (1998); Rosa (2004); Pimenta (1994); among others. International literature: Shulman (2005); Tardif (2007); Vázquez (2007). The data were obtained through semi-structured interviews with the participation of ten UFG s biology s teachers, ahead of disciplines given to the common core core-specific curriculum. In interviews with teachers we sought to identify the conceptions of teaching and the teaching/learning process, the kind of teaching it is intended to give to the graduated, and the elements used as references to their disciplines and classes. From the analysis it may be concluded that, based on the perspective of teaching, most of the teachers do not articulate theoretical knowledge to the practical one so as to have a critical and conscious performance committed to professionalization and to the changes caused by this one in their social environment.